2016
DOI: 10.4314/rj.v3i1.5f
|View full text |Cite
|
Sign up to set email alerts
|

Community Health Workers’ knowledge, attitudes and practices about malaria prevention in Gicumbi District, Rwanda

Abstract: Background: Community Health Workers (CHWs) have significantly contributed to the decrease of malaria prevalence and related mortality among under five children in Rwanda. This study aimed to explore the knowledge, attitudes and practices of CHWs about malaria prevention in a selected District of Rwanda. Methods: A descriptive method, using self administered questionnaires, was used for data collection from 65 respondents of one randomly selected Sector in Gicumbi District, Rwanda. Results: The majority of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
3
11
2
Order By: Relevance
“…(94.4%) (Abate et al, 2013) and Oyekale (85.0%) in other African countries (Oyekale 2015). In this study, 82.4% of the respondents felt that biomedicine was important for treating malaria; this was supported by some previous studies (Sanjana et al, 2006), (Habimana et al, 2016) and (Atulomah et al, 2014). In contrast, a study conducted in Nepal revealed that respondents preferred to consult traditional healers (Joshi et al, 2008).…”
Section: Discussionsupporting
confidence: 79%
“…(94.4%) (Abate et al, 2013) and Oyekale (85.0%) in other African countries (Oyekale 2015). In this study, 82.4% of the respondents felt that biomedicine was important for treating malaria; this was supported by some previous studies (Sanjana et al, 2006), (Habimana et al, 2016) and (Atulomah et al, 2014). In contrast, a study conducted in Nepal revealed that respondents preferred to consult traditional healers (Joshi et al, 2008).…”
Section: Discussionsupporting
confidence: 79%
“…Lastly, our study seems to support findings of a descriptive study done among grass root workers in Rwanda 16 where awareness was found to be significantly associated with their practices regarding malaria diagnosis, treatment and control.…”
Section: Discussionsupporting
confidence: 89%
“…Likewise, (99.2%) study participants recognized that LLINs were used to avoid the bites of mosquitoes. The different training and health educations given by health workers and community health workers at health centers and within the community as supported by [21] in their study were the result of respondents' high level of knowledge. The pregnant women were reported to be not knowing that insecticides are infused in LLINs are and contraindicated to wash them many times a year as argued by.…”
Section: Knowledge On Llinmentioning
confidence: 87%